Why do borrowers make mortgage refinancing mistakes? - Sumit Agarwal; Richard J. Rosen; Vincent Yao (Federal Reserve Bank of Chicago, 2013)
Refinancing a mortgage is often one of the biggest and most important financial decisions that people make. Borrowers need to choose the interest rate differential at which to refinance and, when that differential is reached, they need to take the steps to refinance before rates change again. The optimal differential is where the interest saved by refinancing equals the sum of refinancing costs and the option value of refinancing. Using a unique panel data set, we find that approximately 59% of borrowers refinance sub-optimally - with 52% of the sample making errors of commission (choosing the wrong rate), 17% making errors of omission (waiting too long to refinance), and 10% making both errors. Financially sophisticated borrowers make smaller mistakes, refinancing at rates closer to the optimal rate and waiting less after mortgage rates reach the borrowers' trigger rates. Evidence suggests borrowers learn from their refinancing experiences as they make smaller mistakes on their second refinancing than on their first one.
Keywords: G11; G21; 330; Household Finance; Mortgages; Refinance; Option Value; Financial Crisis; Rational Inattention